Foot wound risk and quality of life of people with type 2 diabetes are related to self-care - Rocha, Rebeca Barbosa da; Silva, Cristiano Sales da; Campelo, Bruna Larysse Diógenes; Pedro, Ana Cristina Marques; Sousa, Fernanda Mello da Silva; Cardoso, Vinicius Saura (ABCS Health Sciences, 2023)
Introduction: Adherence to self-care has been identified as a means of preventing diabetic foot wounds, positively influencing the clinical outcomes and quality of life of patients. The adherence to this strategy is divergent in different populations. It is essential to determine the self-care practices that are associated with diabetic foot ulcers and the quality of life in adults with diabetes. Objective: To understand self-care practices and explore their relationship with the foot wound risk and quality of life of persons with type 2 diabetes in a city in northeastern Brazil. Methods: A descriptive exploratory study was conducted with a sample of 300 individuals with type 2 diabetes. Data were collected using a sociodemographic questionnaire, classification of foot wound risk, the Summary of Diabetes Self-Care Activities, and SF-36. Results: Adherence to self-care was low for physical exercise, self-monitoring of blood glucose, and foot care. The diet and the use of medication had better adherence by the participants. Foot wound risk was related to no adherence to diet (OR 2.2 95% CI 1.32-3.38), physical activity (OR 0.49 95% CI 0.25-0.95), and blood glucose checking (OR 5.31 95% CI 1.58-17.78). Quality of life was associated with physical activity (OR 0.35 95% CI 0.16-0.74). Conclusion: It can be concluded that is a relationship between self-care practices adherence, risk of foot wounds, and quality of life.